2017
DOI: 10.1364/boe.8.004061
|View full text |Cite
|
Sign up to set email alerts
|

Dual-stage deep learning framework for pigment epithelium detachment segmentation in polypoidal choroidal vasculopathy

Abstract: Worldwide, polypoidal choroidal vasculopathy (PCV) is a common visionthreatening exudative maculopathy, and pigment epithelium detachment (PED) is an important clinical characteristic. Thus, precise and efficient PED segmentation is necessary for PCV clinical diagnosis and treatment. We propose a dual-stage learning framework via deep neural networks (DNN) for automated PED segmentation in PCV patients to avoid issues associated with manual PED segmentation (subjectivity, manual segmentation errors, and high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…More recently, some groups have extended their models to perform segmentation of pigment epithelium detachment (PED), the formation of a potential space between the retinal pigment epithelium (RPE) and Bruch's membrane. 196,197 Schmidt-Erfurth et al have reported the correlation of PED metrics with visual acuity in patients with neovascular AMD using a DL-based system. 198 Detailed description and validation of this PED segmentation approach has not yet been published but it appears to treat PED as a single entity rather than a range of specific subtypes.…”
Section: Pigment Epithelium Detachment Subretinal Hyperreflective Mamentioning
confidence: 99%
“…More recently, some groups have extended their models to perform segmentation of pigment epithelium detachment (PED), the formation of a potential space between the retinal pigment epithelium (RPE) and Bruch's membrane. 196,197 Schmidt-Erfurth et al have reported the correlation of PED metrics with visual acuity in patients with neovascular AMD using a DL-based system. 198 Detailed description and validation of this PED segmentation approach has not yet been published but it appears to treat PED as a single entity rather than a range of specific subtypes.…”
Section: Pigment Epithelium Detachment Subretinal Hyperreflective Mamentioning
confidence: 99%
“… 9 14 More recently, machine learning and deep learning methods have been used, including support vector machines, 15 , 16 random forest classifiers, 17 patch-based classification with convolutional neural networks 18 22 or recurrent neural networks, 20 , 22 semantic segmentation with fully convolutional (encoder–decoder) networks, 22 26 and other deep learning methods. 27 30 Importantly, some of these methods have been applied to OCT images from patients with age-related macular degeneration, 18 , 20 , 24 , 27 diabetic retinopathy, 11 , 25 macular telangiectasia type 2, 29 diabetic macular oedema, 13 , 23 , 24 pigment epithelium detachment, 28 glaucoma, 15 , 30 multiple sclerosis 17 , 26 retinitis pigmentosa, 31 and neurodegenerative diseases. 32 These diseases are characterized by variable thinning of the inner retinal layers (e.g., glaucoma and multiple sclerosis), thickening or cystic changes in the nuclear layers (e.g., macular telangiectasia type 2 and diabetic retinopathy) or focal disruption of the retinal pigment epithelium (RPE, e.g., age-related macular degeneration, macular telangiectasia, and pigment epithelium detachment).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the algorithm detected all urgent referral cases within the patient cohort [82]. With the development of DL, some researchers have extended their algorithms to perform segmentation of pigment epithelium detachment, fluid and vessels [83][84][85].…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 99%